Internalisasi Pendidikan Karakter Religius Melalui Budaya Sekolah Di SD - Farleni, Fenti; Sholeh Hidayat; Ujang Jamaludin; Suroso Mukti Leksono (Elementary Teacher Education Program, Majalengka University, 2023)
The purpose of this study was to describe the internalization of religious character education through school culture at SD Suarna, Serang District, Banten Province. This research is a qualitative research with a descriptive approach. The research subjects were school principals, teachers, and students of SD Suarna, Serang District, Banten Province. Data was collected through interviews, observation and documentation studies. Data analysis was carried out through the stages of data collection, data reduction, presentation, and conclusions. The results of this study indicate the internalization of religious character at SD Suarna, Serang District, Banten Province, using school culture and the school's vision and mission as platforms. Obstacles that arise in the process of internalizing religious character come from external factors which include a lack of supervision at home and limited time while at school. While internal factors include students' desires, beliefs, and instincts. The conclusion of this study is that school culture takes place continuously which without realizing it can foster religious character in students. Internalization is not coercive.